An Arm‐First Approach to Cleavable Mikto‐Arm Star Polymers by RAFT Polymerization. Issue 8 (6th February 2014) - Wei, Xiaohu; Moad, Graeme; Muir, Benjamin W.; Rizzardo, Ezio; Rosselgong, Julien; Yang, Wantai; Thang, San H.
<x xml:space="preserve">Abstract</x> Redox‐cleavable mikto‐arm star polymers are prepared by an "arm‐first" approach involving copolymerization of a dimethacrylate mediated by a mixture of macroRAFT agents. Thus, RAFT copolymerization of the monomers BMA, DMAEMA, and OEGMA, with the disulfide dimethacrylate cross‐linker (DSDMA), bis(2‐methacryloyl)oxyethyl disulfide, mediated by a 1:1:1 mixture of three macroRAFT agents with markedly different properties [hydrophilic, poly[oligo(ethylene glycol) methacrylate]—P(OEGMA)8–9; cationizable, poly[2‐(dimethylamino)ethyl methacrylate]—P(DMAEMA); hydrophobic, poly(n‐butyl methacrylate)—P(BMA)] provides low dispersity mikto‐arm star polymers. Good control (Đ < 1.3) is observed for the target P(DMAEMA)/P(OEGMA)/P(BMA) (3:3:1) mikto‐arm star, a double hydrophilic P(DMAEMA)/P(OEGMA) (3:3) mikto‐arm star and a hydrophobic P(BMA) homo‐arm star. However, Đ for the target mikto‐arm stars increases with an increase in either the ratio [DSDMA]:[total macroRAFT] or the fraction of hydrophobic P(BMA) macroRAFT agent. The quaternized mikto‐arm star in dilute aqueous solution shows a monomodal particle size distribution and an average size of ≈145 nm. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>